Gregor and the marks of secret - Collins, Suzanne (New York, NY : Scholastic, 2006)
Twelve-year-old Gregor returns to the world beneath New York City, where he joins forces with Princess Lexa and Ripred the rat to defend the Under landers and the Nibblers from the army led by the adolescent rat king, the Bane.